2015
DOI: 10.1080/10942912.2015.1045515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Position and Storage Duration on the Textural Properties of Eggplant

Abstract: Eggplant has a very limited shelf life and, like other vegetables, is susceptible to different types of damage during and after harvest operations. Besides, according to the inner construction of eggplant fruit, it can be regarded as an inhomogeneous system. It is therefore important to specify how storage might affect their mechanical properties and how they vary in morphology.In this work, eggplants were divided into three portions along the longitudinal axis and their textural properties were separately inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In contrast, studies reported that puncture forces declined at low moisture content because as the moisture level drops, the pectin present in the skin gets degraded, eventually, it loosens the cell wall (Ekrami‐Rad et al, 2011). Similarly, the extensibility of fibers gets reduced at low moisture content, and the fibers do not extend too far and shatter with less force; thus, the puncture force value becomes less (Miraei Ashtiani et al, 2016). Moisture loss induces cell tugor reduction, which can also lead to a change in puncture force with respect to moisture.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, studies reported that puncture forces declined at low moisture content because as the moisture level drops, the pectin present in the skin gets degraded, eventually, it loosens the cell wall (Ekrami‐Rad et al, 2011). Similarly, the extensibility of fibers gets reduced at low moisture content, and the fibers do not extend too far and shatter with less force; thus, the puncture force value becomes less (Miraei Ashtiani et al, 2016). Moisture loss induces cell tugor reduction, which can also lead to a change in puncture force with respect to moisture.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in water loss may also cause a decrease in hardness (Oz et al., 2015). Since cells with high humidity have high flexibility and extensibility and this condition allowed them to resist the forces (Miraei Ashtiani et al., 2015) occurred during transportation.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is crucial factor to have the knowledge of the agricultural products' mechanical properties, during the design, construction, and applications of agricultural robots (Ekruyota and Uguru, 2021;Uguru and Akpenyi-Aboh, 2021). Relevant data on the physic-mechanical and textural properties of fruits are vital tool in the workout plan of better robot grippers, for optimum area gripped by the robot on the fruit's surface (Ashtiani et al, 2016). Areas found in the research literature where the physical and the mechanical properties has been applied is in two tomato cultivars used for the design and utilization of tomato fruit harvesting robot (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physical and micromechanical properties of tomato fruit's epicarp and mesocarp, which are useful in the production of harvest and post-harvest unit operations robots, were studied by Arazuri et al (2007) and Gladyszewska and Ciupak (2009). Ashtiani et al (2016) investigated some engineering properties of eggplant (cv. Siah-e-Mashhad) fruits, concerning the fruit's region (part) and orientation, which are essential in the design and applications of robots.…”
Section: Introductionmentioning
confidence: 99%